Path Selection of Climate Change Litigation from the Perspective of the Risk Prevention Principle - Wang, Jing; Sun, Qingling (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
Before China achieves the “dual carbon” goal, the judicialization of climate change is also a practical need to ensure that China achieves the two goals of “carbon peak” and “carbon neutrality”. At present, the issue of climate change has entered the legal regulation stage, and owing to its inherent global nature and high degree of uncertainty, the law has exposed the shortcomings of insufficient regulation and difficulty in meeting the needs of climate change. At present, there has been heated discussion on the construction of the litigation path of climate change litigation, and it is also meaningful to study litigation path selection in climate change litigation from the perspective of the risk prevention principle. Therefore, this paper discusses the litigation path of climate change litigation to effectively prevent environmental risk from the perspective of the principle of risk prevention on the basis of existing research on the litigation path of climate change litigation in the academic field and with reference to litigation models of environmental public interest litigation and air pollution public interest litigation.